Serological Evidence of Filovirus Infection in Nonhuman Primates in Zambia - Changula, Katendi (Viruses, 2021)
Ebolaviruses and marburgviruses are filoviruses that are known to cause severe hemorrhagic fever in humans and nonhuman primates (NHPs). While some bat species are suspected to be natural reservoirs of these filoviruses, wild NHPs often act as intermediate hosts for viral transmission to humans. Using an enzyme-linked immunosorbent assay, we screened two NHP species, wild baboons and vervet monkeys captured in Zambia, for their serum IgG antibodies specific to the envelope glycoproteins of filoviruses. From 243 samples tested, 39 NHPs (16%) were found to be seropositive either for ebolaviruses or marburgviruses with endpoint antibody titers ranging from 100 to 25,600. Interestingly, antibodies reactive to Reston virus, which is found only in Asia, were detected in both NHP species. There was a significant difference in the seropositivity for the marburgvirus antigen between the two NHP species, with baboons having a higher positive rate. These results suggest that wild NHPs in Zambia might be nonlethally exposed to these filoviruses, and this emphasizes the need for continuous monitoring of filovirus infection in wild animals to better understand the ecology of filoviruses and to assess potential risks of outbreaks in humans in previously nonendemic countries.